2008
DOI: 10.1124/jpet.107.135079
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Monoamine Transporters by Common Biogenic Amines via Trace Amine-Associated Receptor 1 and Monoamine Autoreceptors in Human Embryonic Kidney 293 Cells and Brain Synaptosomes

Abstract: In brain monoaminergic systems, common biogenic amines, including dopamine, norepinephrine, and serotonin, serve as neurotransmitters. Monoamine autoreceptors provide feedback regulation in neurotransmitter release, and monoamine transporters clear the released neurotransmitters to control synaptic signaling. Recently, trace amine-associated receptor 1 (TAAR1) has been found to be expressed in brain monoaminergic nuclei and activated by common biogenic amines in vitro. This study used transfected cells and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 36 publications
(53 reference statements)
4
97
1
Order By: Relevance
“…However, after MFB 6-OHDA injections, a near-complete loss of TH levels was found in both genotypes, indicating that the partial survival of dopaminergic neurons is required for this effect of TAAR1. Consistent with our finding of enhanced DAT levels in TAAR1 KO mice, previous in vitro studies in brain synaptosomes and transfected cells have reported that activation of TAAR1 internalizes DAT from the cell membrane, inhibits dopamine reuptake, and enhances dopamine efflux via DAT reversal Xie et al, 2008), However, because 6-OHDA elicits its neurotoxic effects by entering the neuron via DAT, the finding of a more pronounced reduction of TH in TAAR1 KO compared with WT mice was unexpected. These studies were extended to experiments examining the effects of a TAAR1 agonist, RO5166017, on reduction of DAT by intrastriatal 6-OHDA administration in WT mice.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, after MFB 6-OHDA injections, a near-complete loss of TH levels was found in both genotypes, indicating that the partial survival of dopaminergic neurons is required for this effect of TAAR1. Consistent with our finding of enhanced DAT levels in TAAR1 KO mice, previous in vitro studies in brain synaptosomes and transfected cells have reported that activation of TAAR1 internalizes DAT from the cell membrane, inhibits dopamine reuptake, and enhances dopamine efflux via DAT reversal Xie et al, 2008), However, because 6-OHDA elicits its neurotoxic effects by entering the neuron via DAT, the finding of a more pronounced reduction of TH in TAAR1 KO compared with WT mice was unexpected. These studies were extended to experiments examining the effects of a TAAR1 agonist, RO5166017, on reduction of DAT by intrastriatal 6-OHDA administration in WT mice.…”
Section: Discussionsupporting
confidence: 79%
“…It seems that TAAR1 is expressed, not only in nerve cells, but also in glia because a recent study reported that TAAR1 activation on human astrocytes can decrease glutamate clearance in vitro via downregulation of EAAT-2 expression (Cisneros and Ghorpade, 2014). There is also a need for more precise information on the subcellular localization of TAAR1 in intact cells, especially because several experiments in transfected HEK293 cells have indicated that TAAR1 is mainly localized intracellularly (Bunzow et al, 2001;Miller et al, 2005;Xie et al, , 2008. Future studies are needed to determine whether a cytosolic localization of TAAR1 causes specific effects on intracellular signaling with relevance to neurotransmitter release.…”
Section: Possible Molecular and Cellular Actions Of Taar1mentioning
confidence: 99%
“…TAAR1 mRNA expression in the mesocorticolimbic system TAAR1 mRNA has been found in the limbic system, cortices, and monoaminergic system of the mammalian brain (Borowsky et al, 2001;Bunzow et al, 2001;Miller et al, 2005;Lindemann et al, 2008;Xie et al, 2008;Espinoza et al, 2015a). Consistent with this, using real-time PCR method, the present study also showed that TAAR1 mRNA was expressed in the VTA, SN, mPFC, NAc, and amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…There are few examples that support the notion of a direct GPCR/channel (Yekkirala 2013) or GPCR/transporter interactions, e.g. the observed interplay between the ADRB2, GLUT4 and melatonin 1 receptor/Cav 2.2 (Dehvari et al 2012, Benleulmi-Chaachoua et al 2016, or modulation of monoamine transporters by common biogenic amines via the TAAR1 (Xie et al 2008). Altogether, this raises the possibility that an association between different proteins and GPCRs should be of importance due to a fast mutual or synergistic influence on functional properties.…”
Section: Existence Of Direct Interactions Between Gpcrs/ion Channels mentioning
confidence: 99%